Perlindungan Hukum Terhadap Konsumen Akibat Wanprestasi dalam E-Commerce Ditinjau dari Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Rahmani Hasanah, Imma (Rechtsregel : Jurnal Ilmu Hukum, 2024)
An agreement is an event where a person promises to another person or where two people promise each other to carry out an agreement. An agreement is a legal relationship regarding property between two parties, in which a party promises or is deemed to have promised to do something. This research is entitled Legal Protection for Consumers Due to Default in Precious Metal Electronic Transactions in terms of Law Number 8 of 1999 concerning Consumer Protection. The purpose of this study is to find out how to protect consumers in electronic transactions in the event of a default. This study uses empirical or field research methods and is supported by primary data sources as a literature review including Law Number 8 of 1999 concerning Consumer Protection. In this study, a field approach was applied by means of interviews and observations of the parties involved in the transaction. The provisions that protect consumer rights in these laws and regulations have not been properly utilized by consumers who experience default. With the development of the internet at this time, a virtual trading system has been built. E-Commerce or electronic commerce are all forms of trade transactions of goods or services that use internet intermediary media. With online or electronic shopping, it makes it easier for many parties in terms of transactions. However, there are still many people who want to act dishonestly around us. So that Indonesian law also prepares laws to ensnare perpetrators of fraud in electronic transactions (e-commerce). This study concludes that electronic transactions must still refer to the law as a guide in applying the rule of law, and the parties carrying out these activities must be responsible and if there is a default in the transaction activity, it must be resolved without harming the other party.